Qualitative risk assessment of HPAI H5N1 transmission between small-scale commercial broiler chicken farms in Bogor, Indonesia - Idris, Syafrison; Palupi, Maria Fatima; Sudiana, Elly; Unger, Fred; Costard, Solenne; Pfeiffer, Dirk (International Food Policy Research Institute, 2010)
As part of the DFID-funded Pro-Poor HPAI Risk Reduction Project, a qualitative risk assessment was conducted for risk questions agreed during a stakeholder workshop in November, 2008, related to transmission of HPAI H5N1 between small-scale commercial broiler farms in the District and Municipality of Bogor. The overall risk of transmission was assessed as low, and risk estimates for the different pathways range from negligible to low. The risk associated with movement of contaminated visitor and equipment exchange was assessed as the highest. The risk of transmission via free-ranging poultry and wild birds was assessed negligible to very low, while via other pathways was assessed as negligible. It is important to note that the risk was estimated low because of a conditional probability effect (risk of infection/prevalence of HPAI H5N1 in small-scale broiler farm when data were collected was low). However, there are many steps/mechanisms of transmission associated with higher risk. It is highlighted that increasing prevalence of HPAI H5N1 in broiler farms will lead to increasing of risk of transmission. All risk estimates, except the one considering transmission via manure, were associated with a high uncertainty because of the lack of data on both the poultry sector in Indonesia and the epidemiology of HPAIV H5N1 more generally.